Geoarchaeology in an urban context: The town of Reggio Emilia and river dynamics during the last two millennia in Northern Italy. Issue 1 (7th November 2017) - Cremaschi, Mauro; Storchi, Paolo; Perego, Alessandro
Abstract: On the grounds of geomorphological evidence, core stratigraphy, and archaeological and historical sources, the relationships between the urban development of Reggio Emilia (Po River plain, Northern Italy) and the adjoining Crostolo River are reconstructed over the last two millennia. The town of Reggio Emilia was established in the second century B.C. along the Crostolo River, but geographic relationships between river and town changed several times because of the collective effects of human activity, geological processes, and climatic change. The course of the Crostolo was artificially diverted outside Reggio Emilia during the Roman age and in the years A.D. 1250 and A.D. 1571, largely because of westward stream migration. This progressive shift was triggered by the neotectonic activity of buried folded thrusts. Vertical displacements resulted in uplift and conversely in the subsidence of Reggio Emilia's northwest margin. Stream migration patterns were thereby displaced westward. Climate change also affected the behavior of the Crostolo River as increased flooding during the early Medieval period and consequent channel instability underpinned engineering efforts to rechannel stream flow via a canal built along the city walls in A.D. 1571 at the onset of the Little Ice Age.